PERAN KECERDASAN EMOSIONAL DALAM PEMBELAJARAN JARAK JAUH - Desmita; Syafri Doni Putra, S.D (Fakultas Psikologi Universitas Borobudur, 2024)
Distance learning is very dependent on the interest and seriousness of students to follow and be actively involved in online learning activities. Educators are of course very limited in observing student learning activities through online platforms. Network connection constraints, dependence on electrical resources are very vital obstacles in distance learning, so that it becomes an opening for students not to be actively involved in distance learning. Therefore, the implementation of data distance learning runs well when there is participation and seriousness and interest from students to actively participate. Researchers want to try to find the role of emotional intelligence of students in participating in distance learning. The research method uses literature study, supported by factual data from interviews and observations at school. The results showed that the level of emotional intelligence of students in participating in distance learning is very urgent. Students are expected to be able to divide their time, have awareness of duties and responsibilities, and have high motivation to follow and be active in seeking learning information. In addition, it is also hoped that students can empathize with each other and interact with other students in group study. So thus emotional intelligence in distance learning greatly influences the learning process and learning outcomes, and is evidence of students' readiness to apply distance learning.